2022
DOI: 10.2174/1389450123666220906091432
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on Liver Targeting: Emphasis on Nanotechnology- based Molecular Targets and Receptors Mediated Approaches

Abstract: Background: The pathogenesis of hepatic diseases involves several cells which makes the delivery of pharmaceutical agents complicated. Many severe liver diseases affecting the worldwide population cannot be effectively treated. Major hindrance or challenges faced are natural physiological barriers and non-specific targeting of drugs administered leading to inefficient treatment. Hence, there is an earnest need to look for novel therapeutic strategies which can overcome these hindrances. Kind of literature have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 140 publications
0
1
0
Order By: Relevance
“…Specifically, it was reported that there are present 20,000–25,000 MRs per cell on the LSECs [ 173 , 174 ]. The representative ligands of the MR include mannose, N-acetylglucosamine, and N-acetylgalactosamine (GalNAc) [ 175 ]. MR has been considered a favorite target for hepatic drug delivery because of the presence of MR in LSECs.…”
Section: Strategies To Enhance the Efficacy Of Nafld Drug Candidatesmentioning
confidence: 99%
“…Specifically, it was reported that there are present 20,000–25,000 MRs per cell on the LSECs [ 173 , 174 ]. The representative ligands of the MR include mannose, N-acetylglucosamine, and N-acetylgalactosamine (GalNAc) [ 175 ]. MR has been considered a favorite target for hepatic drug delivery because of the presence of MR in LSECs.…”
Section: Strategies To Enhance the Efficacy Of Nafld Drug Candidatesmentioning
confidence: 99%
“…However, further toxicology and pharmacology studies are required to ensure that the breakdown and degradation of nanomaterials in small and large animal models do not have any adverse effects. Such studies are critical for future applications and translation of this technology to humans [146][147][148] . The toxicity of the nanomaterials being studied for ED research still needs to be understood.…”
Section: Use Of Nanotechnology In Erectile Dysfunctionmentioning
confidence: 99%